The Inuit as geographers: The case of Eenoolooapik - Jones, H. (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2004)
AbstractRecent studies reveal an increasing number of instances in which Qallunaat benefited from Inuit knowledge of the lands and waters upon which they had lived for centuries. One of the best recorded examples of Inuit geographical knowledge is found in the story of Eenoolooapik, who led to the European rediscovery of Cumberland Sound 250 years after it was first explored and named by John Davis. Taken as a young man from Baffin Island to Scotland in 1839, Eenoolooapik excited whaling captain William Penny with stories of a large, whale-rich body of water then unknown to European and American whalers. “Eenoo,” as he was popularly called, drew a map of the coastline of eastern Baffin showing a deep bay known by the Inuit as “Tenudiackbeek,” and upon their return the next summer, Penny skeptically followed Eenoolooapik’s directions into a large bay in which the Inuk had spent his childhood. Thus the youngster’s geographical knowledge of his homeland resulted in the opening to whalers of a long-lost body of water in which, in the next decade, shore stations were established that offered seasonal employment to the Inuit and dramatically changed their lives. The story of Eenoolooapik is told in a small book by Alexander M’Donald, A Narrative of Some Passages in the History of Eenoolooapik […] published in Edinburgh in 1841. This is probably the only nineteenth-century full-length biography of an Inuk published during the subject’s lifetime; and because copies of the book are exceedingly rare, the following article provides a synopsis as a means of portraying more fully the geographical contributions of Eenoolooapik.